ASSESSING ORONASAL FISTULA RATES: MINIPLATE AS EXTERNAL FIXATOR VS ANTERIOR NASAL SPINE PLATING FOR PALATAL FRACTURES - Ain-us-Saba; Muhammad Umar Farooq; Fouzia Aslam; Hamza Hassan Mirza; Abdul Manan Shahid; Muhammad Asad Javed (Journal of Ayub Medical College Abbottabad, 2024)
Background: Palate, a midface bone, shapes the face and supports buttresses. Palatine process of maxilla and horizontal plate of palatine bone constitute it. Palatal bone is thicker anteriorly and laterally than posteriorly and centrally. Palatal fractures occur with maxillary fractures. Palatal-maxillary fractures occur 8-46.4% of the time.2,5 Palatal fractures can cause palatal ecchymosis in closed fractures and upper lip, palatal mucosa, incisor tooth loss, or occlusal disruption in displaced fractures. The objective was to determine the surgical outcome of palatal fractures with locking plates as external fixator vs. alveolar plating in terms of frequency of oronasal fistula formation. Methods: A Randomized control trial was carried out in Department of Oral and Maxillofacial surgery, Pakistan Institute of Medical Sciences, Islamabad. between 14th July, 2017 to 14th July, 2018. Lottery split patients into groups A and B. Data was collected on designed questionnaire and was entered and analyzed using SPSS v22. Chi-square was applied to check the association. Results: A total of 130 patients were enrolled in the trial based on the predefined inclusion criteria. The average age of participants in the research was 41.16 years with a standard deviation of 10.44. Of the total participants, 88 (67.7%) were male and 42 (32.3%) were female, as per the inclusion criteria. The occurrence rate of oronasal fistula development in both groups, namely palatal fractures treated with locking plates as an external fixator vs alveolar plating, was 1 (1.5%) and 7 (10.8%) respectively. This difference was found to be statistically significant with a p-value of 0.029. Conclusion: Osteosynthesis using 2.0 mm locking plates as external fixator had a lower rate of oronasal fistula than alveolar plating. Future investigations at numerous configurations are needed to determine which approach is best. such that a regular strategy will reduce infection, fistula development, and necrosis afterwards